PERANCANGAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) PADA ATAP GEDUNG WISTI SABHA BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI - Purna Suartawan, Gede; Dwi Giriantari, I. A.; Sukerayasa, I Wayan; Ariastina, Wayan Gede; Setiawan, I Nyoman; Satya Kumara, I Nyoman (Program Studi Teknik Elektro UNUD, 2024)
The installed PLTS capacity in Bali is currently still 3.44% of the target given by the General National Energy Plan (RUEN) of 108 MWp in 2025. The island of Bali has limited land availability so rooftop PLTS is a solution. The design of the rooftop PLTS was carried out on the roof of the Wisti Sabha Building at I Gusti Ngurah Rai International Airport. The research uses PVSyst simulation software while the investment feasibility method uses the Benefit-Cost Ratio (BCR), Net Present Value and discounted payback period (DPP) methods. Based on the simulation results, the rooftop PLTS capacity is 56.6 kWp with energy production of 98,009 kWh/year. The B-CR value obtained is 2.23, the net present value is IDR 707,436,838.55 and the DPP is 7 years, with a rooftop solar system life of 25 years.